Identitas Spesies Botrytis pada Tanaman Hortikultura Di Jawa Barat, Indonesia - devi ayu komalaningrat; Efi Toding Tondok; widodo widodo (Jurnal Fitopatologi Indonesia, 2018)
Identity of Botrytis Species on Horticultural Crops In West Java, IndonesiaBotrytis species are economically important pathogens with a very broad host range including more than 200 horticultural crops. The identity of these fungus found  in Indonesia has not been investigated and need to be reconfirmed due to the species variations of Botrytis found worldwide. The aims of this research were to identify Botrytis species infecting crops in West Java based on its morphology and molecular characteristics, as well as its pathogenicity traits. Based on morphological characters, all 25 isolates found were identified as B. cinerea. ITS-based sequences of the 8 isolates showed 96-100% similarity to reported B. cinerea in GenBank. The phylogenetic analysis confirmed that all collected B. cinerea were grouped in the same cluster with Australia, Netherlands, and other Asian region isolates. Pathogenicity tests using strawberry fruits demonstrated that all isolates were pathogenic as indicated by grey mold symptom development; the isolates from orchid showed the highest virulence. This research is the first report confirming Botrytis cinerea identity based on morphology and molecular methods in Indonesia, and also confirmed B. cinerea as the only species of Botrytis found in West Java.